Perceived usefulness and ease of use of websites : evidence of the impact of website design features / Dennis Taylor and Nicky Brownfield - Dennis, Taylor; Nicky, Brownfield (Faculty of Accountancy & Accounting Research Institute (ARI), 2002)
This study reports on an empirical investigation of accounting students' satisfaction with design features of websites they use for study purposes. An internet website evaluation service is sourced to establish a set of website design features. User satisfaction is measured by the surrogates of perceived usefulness (PU) and perceived ease of use (PEOU). To date, empirical studies of PU and PEOU have not been extended to the use of websites. Drawing on the instruments developed by Davis (1989) and replicated by Adams et al (1§92) and Subramanian (1994), this study administers a questionnaire to 92 second and third year undergraduate accounting students. The results give support to the hypothesis that each of the particular website features of contents, links, graphics, attractiveness, search engines, selling message and uniqueness is related to accounting students' PU of websites. By comparison, students' PEOU of websites was found to be largely unaffected by the importance they place on particular website features. The findings have practical implications for website developers who are contemplating design features to incorporate in their websites to best attract accounting students who are gathering information for assignments, projects and other study purposes.